Pengaruh Konsep Diri terhadap Kematangan Karir Siswa Kelas 12 SMK Negeri di Kabupaten Bandung - Tazkia Diva Sastradireja; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2022)
Abstract. Vocational High School is an educational institution that prepares students to compete when entering the world of work after graduation. However, based on data on the open unemployment rate according to the Badan Pusat Statistik (2022), the unemployment rate in Indonesia is dominated by vocational high school graduates. The unemployment rate is related to an individual's career maturity, because at a certain individual age effectively completes and copes with tasks related to their career development (Super, 1980). Because it describes the individual through what is obtained from interaction with the environment, the self-concept is one of the predictive elements that can affect career maturity (Calhoun et al., 1995). Based on this background, the Researcher wanted to find out the influence of self-concept on the career maturity of 12th grade Vocational High School students. This study used a simple random sampling technique with 420 students as sample. The self-concept measurement tool is a development that has been adapted by Almaida et al. (2019) with a reliability value of 0.691, and a career maturity measurement tool has been adapted by Masmuhazir (2017) with a reliability value of 0.891. Data analysis using simple linear regression resulted in a positive and significant effect, with a regression coefficient value of 0.535 and a significance of 0.000 (p < 0.05). The value of the coefficient of determination (R2) in this study is 0.370. This means that self-concept contributes 37% to career maturity, while 67% is influenced by other factors not disclosed in this study. Abstrak. Sekolah Menengah Kejuruan merupakan lembaga pendidikan yang menyiapkan siswanya dapat bersaing saat memasuki dunia kerja setelah lulus. Namun, berdasarkan data tingkat pengangguran terbuka menurut Badan Pusat Statistik (2022), angka pengangguran di Indonesia didominasi oleh lulusan Sekolah Menengah Kejuruan. Tingkat pengangguran berkaitan dengan kematangan karir individu, karena pada usia tertentu secara efektif menyelesaikan dan mengatasi tugas-tugas yang berkaitan dengan perkembangan karirnya (Super, 1980). Karena menggambarkan individu melalui yang diperoleh dari interaksi dengan lingkungan, maka konsep diri ialah salah satu elemen prediktif yang dapat mempengaruhi kematangan karir (Calhoun et al., 1995). Berdasarkan latar belakang tersebut, Peneliti ingin mencari tahu bagaimana pengaruh konsep diri terhadap kematangan karir siswa kelas 12 Sekolah Menengah Kejuruan. Penelitian ini menggunakan teknik simple random sampling dengan sejumlah 420 siswa. Alat ukur konsep diri merupakan pengembangan yang sudah diadaptasi oleh Almaida et al. (2019) dengan nilai reliabilitasnya 0.691, serta alat ukur kematangan karir sudah diadaptasi oleh Masmuhazir (2017) dengan nilai reliabilitasnya 0.891. Analisis data menggunakan regresi linear sederhana menghasilkan pengaruh positif dan signifikan, dengan nilai koefisien regresi sebesar 0.535 dan signifikansi 0.000 (p < 0.05). Nilai koefisien determinasi (R2) dalam penelitian ini sebesar 0.370. Artinya, konsep diri memberikan kontribusi sebesar 37% terhadap kematangan karir, sedangkan 67% dipengaruhi oleh faktor lain yang tidak diungkapkan di dalam penelitian ini.